2001
DOI: 10.1080/14733140112331385060
|View full text |Cite
|
Sign up to set email alerts
|

How effective is workplace counselling? A review of the research literature

Abstract: The provision of counselling for work‐related problems has expanded in recent years, as organisations have recognised the value of this approach to staff support. However, there has been relatively little research into the outcomes of workplace counselling, and no systematic reviews have been conducted into the effectiveness of counselling in this setting. This paper presents the results of a preliminary review of evidence in this area. 34 studies of the effectiveness of workplace counselling were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…McLeod's first review concluded that workplace counselling interventions produce a small yet positive impact on work-related outcomes such as job commitment, work functioning and job satisfaction (McLeod, 2001). In addition, McLeod's second review reported that this form of intervention can reduce sickness absence by up to 60% (McLeod, 2008). These conclusions are compromised by the methodological limitations of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…McLeod's first review concluded that workplace counselling interventions produce a small yet positive impact on work-related outcomes such as job commitment, work functioning and job satisfaction (McLeod, 2001). In addition, McLeod's second review reported that this form of intervention can reduce sickness absence by up to 60% (McLeod, 2008). These conclusions are compromised by the methodological limitations of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Brief psychological counseling has been studied frequently and, according to McLeod and McLeod's (2001) review of this literature, can be effective. Whether helping employees find child care reduces stress caused by difficulty finding child care has not been formally assessed; it nevertheless would seem to be a direct and highly plausible solution to that source of stress.…”
Section: Body and Soulmentioning
confidence: 99%
“…For instance, businesses might find that returns on investments increase as a result of employer-subsidized ill-being interventions. Indeed, businesses might already be crunching these numbers (Hargrave & Hiatt, 2005;Hargrave, Hiatt, Alexander, & Schaffer, 2008;McLeod, 2010;McLeod & Mcleod, 2001;Stewart, Ricci, Chee, Hahn, & Morganstein, 2003).…”
Section: Practical Utilitymentioning
confidence: 99%